Konseling Kelompok Rasional Emotif Perilaku dalam Membantu Mengatasi Regulasi Emosi Siswa SMP, Efektivkah? - Habsy, Bakhrudin All; Faricha, Ifta Nur; Suroso, Dimas Heri (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2019)
This study aims to examine the effectiveness of Rational Emotive Behavior group counseling. Based on this, the research counseling is effective to improve emotional regulation, especially for junior high school students. This study is using the Nonequivalent Control Group Design which is then analyzed using a nonparametric statistical test, i.e Wilcoxon Test. Based on the results of data analysis it is obtained that the z count is -2.707 and the probability number (sig. (2-tailed)) is 0.007. Furthermore, the figure is compared with the z table at a significant level of 0.05 so that it is known as 1.96. Because Z count is wich smaller than z table So it can be concluded that Rational Emotive Behavior group counseling is effective to improve emotional regulation of Junior High School students.